Understanding olfactory dysfunction in the COVID-19 era: insights from a cross-sectional survey of the Saudi community - Aldrees, Turki; Almatrafi, Sharif; Mokhatrish, Mohammad; Aldriweesh, Turki (Frontiers in Public Health, 2023)
Background and Objectives: COVID-19 has emerged as a public health emergency caused by the coronavirus 2 (SARS-CoV2). However, only a few studies have reported that anosmia is an early predictor of COVID-19. Therefore, this study aimed to assess the current level of knowledge regarding smell dysfunction in COVID-19 era in Saudi community.An online survey was conducted using Survey Monkeys in Saudi Arabia. The survey was distributed through Twitter and Whatsapp. The questionnaire included individuals' demographic information, such as sex, age, residence, income, and qualifications, as well as their knowledge of the early symptoms of COVID-19. ANOVA and Mann-Whitney U test were conducted to analyze the data. There were twelwe items on knowledge dimensions which were assessed through five-point Likert scale.In total, 809 respondents completed the questionnaire. Among them, 658 (81.3%) had no knowledge of how sudden loss of or change in the sense of smell can be the only symptom of COVID-19. However, most participants, 738 (91.2%), knew that fever was a symptom of COVID-19. Similarly, 707 (87.4%) and 772 (95.5%) participants knew that cough and shortness of breath were the major symptoms of COVID-19, respectively. In addition, 395 (48.3%) participants had no information regarding taste changes as a symptom of COVID-19. Notably, participants who were female, married, or diagnosed with COVID-19 had significantly greater knowledge of smell-related issues due to COVID-19 than males, unmarried, and healthy/those without COVID-19.This study revealed that the Saudi population has an fairly good level of knowledge regarding common COVID-19 symptoms as more than 90% of the participants understood symptoms of COVID-19, but less acceptable knowledge regarding smell and taste dysfunction as more than 80% had no knowledge of change in olfactory and taste function was due to COVID-19. .